2015
DOI: 10.5774/44-0-186
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Receptive Collocational Competence Across Proficiency Levels

Abstract: The present study investigates (i) English as Foreign Language (EFL) learners' receptive collocational knowledge growth in relation to their linguistic proficiency level; (ii) how much receptive collocational knowledge is acquired as linguistic proficiency develops; and (iii) the extent to which receptive knowledge of collocations of EFL learners varies across word frequency bands. A proficiency measure and a collocation test were administered to English majors at the University of Burundi. The results of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 41 publications
0
23
1
4
Order By: Relevance
“…Although collocation acquisition is a life-long, largely intuition-based process in L2 (Siyanova-Chanturia & Martinez, 2014;Siyanova & Schmitt, 2008), existing research on collocations has identified a number of such factors, which can be classified into two domains. The first domain includes external non-collocation-specific factors: (1) extralinguistic, such as the age of onset and offset of learning English (Granena & Long, 2013;Han, 2004;Wray, 2002); length of residence in an English-speaking country (Bardovi-Harlig & Bastos, 2011;Groom, 2009;Nesselhauf, 2005); language input and output Durrant & Schmitt, 2010;Szudarski & Carter, 2016), and psychological-affective factors of culture and motivation (Li & Schmitt, 2010;Smith, 2005;Wray, 2008); and (2) interlinguistic, such as whether English is used as the predominant language for thinking and communication (Wang & Shih, 2011;Xu, 2015), English language proficiency (Groom, 2009;Laufer & Waldman, 2011;Nizonkiza, 2012Nizonkiza, , 2015Schmitt, 2013), and interlanguage interference (Irujo, 1986;Liao, 2010;Millar, 2011;Peters, 2016;Wolter & Yamashita, 2015).…”
Section: Objectives and Research Questionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Although collocation acquisition is a life-long, largely intuition-based process in L2 (Siyanova-Chanturia & Martinez, 2014;Siyanova & Schmitt, 2008), existing research on collocations has identified a number of such factors, which can be classified into two domains. The first domain includes external non-collocation-specific factors: (1) extralinguistic, such as the age of onset and offset of learning English (Granena & Long, 2013;Han, 2004;Wray, 2002); length of residence in an English-speaking country (Bardovi-Harlig & Bastos, 2011;Groom, 2009;Nesselhauf, 2005); language input and output Durrant & Schmitt, 2010;Szudarski & Carter, 2016), and psychological-affective factors of culture and motivation (Li & Schmitt, 2010;Smith, 2005;Wray, 2008); and (2) interlinguistic, such as whether English is used as the predominant language for thinking and communication (Wang & Shih, 2011;Xu, 2015), English language proficiency (Groom, 2009;Laufer & Waldman, 2011;Nizonkiza, 2012Nizonkiza, , 2015Schmitt, 2013), and interlanguage interference (Irujo, 1986;Liao, 2010;Millar, 2011;Peters, 2016;Wolter & Yamashita, 2015).…”
Section: Objectives and Research Questionsmentioning
confidence: 99%
“…English language proficiency. The majority of researchers connect collocational competence to overall level of L2 proficiency and agree that collocational errors might gradually decrease but never disappear even at the most advanced stages, and that limitations exist for both receptive and productive knowledge (Gitsaki, 1996(Gitsaki, , 1999Groom, 2009;Laufer & Waldman, 2011;Nizonkiza, 2012Nizonkiza, , 2015. However, the specific characteristics of collocational errors differ depending on proficiency level and the pattern is not straightforward.…”
Section: English As the Predominant Language For Communication And Thmentioning
confidence: 99%
See 3 more Smart Citations